Boosting emotional intelligence in the post-Covid. Flexible approaches in teaching social and emotional skills - Alessia Signorelli; Annalisa Morganti; Stefano Pascoletti (Firenze University Press, 2021)
The Covid pandemic has opened new challenges for education, especially for the social and emotional wellbeing of children and adolescents who had to face unprecedented and upsetting changes in their daily lives. The paper explores the possibilities offered by the social-emotional intelligence framework in helping children and youths develop the good emotional literacy needed for facing such a challenging time and growing as wholesome adults. This is done through an in-depth analysis of the concept of replication and generalization and by proposing a perspective working model for embedding social and emotional learning in daily teaching and learning activities.   Promuovere l'intelligenza emotiva nel post-Covid. Approcci flessibili per insegnare le competenze sociali e emotive.   La pandemia di Covid ha introdotto nuove sfide nel mondo dell'educazione, in modo particolare per quanto riguarda il benessere sociale e emotivo di bambini e adolescenti che hanno dovuto affrontare cambiamenti sconvolgenti senza precedenti nel loro vivere quotidiano. L'articolo esplora le possibilità offerte dal costrutto di educazione socio-emotiva a supporto dello sviluppo in bambini e ragazzi di un'alfabetizzazione emotiva solida, necessaria per affrontare un periodo così sfidante e per la loro crescita futura. Tutto questo è fatto attraverso un'analisi approfondita dei concetti di replicabilità e generalizzazione e attraverso la proposta di un nuovo modello di lavoro per integrare l'educazione socio-emotiva all'interno delle azioni didattiche quotidiane